THE CONCEPT OF DETERMINING THE READINESS LEVEL OF ROBOTIC SYSTEMS FOR PERFORMING COMBAT TASKS - LAKTIONOV, OLEKSANDR; PEDCHENKO, NAZAR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article is dedicated to the process of developing a concept for assessing the readiness level of robotic systems for performing combat tasks. It analyzes techniques for establishing the theoretical foundations of concepts and their elements. Based on the results of a comparative analysis, the components of a typical concept’s structure and the prerequisites for their development have been identified. The typical structure of the concept includes principles, models, methods, technologies, and has certain prerequisites that influence its content. Prerequisite 1 relates to the principles of the concept, where specific models can be employed. Prerequisite 2 encompasses aspects of creating methodologies through the enhancement of existing methods. Prerequisite 3 defines the procedure for selecting a particular group of methods, including clustering methods when data distribution information is lacking. A concept for assessing the readiness level of robotic systems for performing combat tasks has been proposed, which is based on principles such as system possibility, unit coordination, optimization of route planning, optimization of target identification and engagement, reliability, safety, diagnostics, and analysis of the system’s environmental conditions. Other components of the proposed concept include action scenarios and action models that depend on the characteristics of input data and allow for the simulation of the expected outcomes of activities. Furthermore, the concept involves the existence of a method for determining the integral readiness level of the robotic system and corresponding software implementation. Among the limitations of the proposed concept, it is important to highlight the absence of a formal description of the research object and the determination of the specifics of the research methodology tools.